Rice breeding for yield under drought has selected for longer flag leaves and lower stomatal density - Kumar, Santosh; Tripathi, Santosh; Singh, Suresh Prasad; Prasad, Archana; Akter, Fahamida; Syed, Md Abu; Badri, Jyothi; Das, Sankar Prasad; Bhattarai, Rudra; Natividad, Mignon A.; Quintana, Marinell; Venkateshwarlu, Challa; et al. (Oxford University Press, 2021)
Direct selection for yield under drought has resulted in the release of a number of drought-tolerant rice varieties across Asia. In this study, we characterized the physiological traits that have been affected by this strategy in breeding trials across sites in Bangladesh, India, and Nepal. Drought- breeding lines and drought-tolerant varieties showed consistently longer flag leaves and lower stomatal density than our drought-susceptible check variety, IR64. The influence of environmental parameters other than drought treatments on leaf traits was evidenced by close grouping of treatments within a site. Flag-leaf length and width appeared to be regulated by different environmental parameters. In separate trials in the Philippines, the same breeding lines studied in South Asia showed that canopy temperature under drought and harvest index across treatments were most correlated with grain yield. Both atmospheric and soil stress strengthened the relationships between leaf traits and yield. The stable expression of leaf traits among genotypes and the identification of the environmental conditions in which they contribute to yield, as well as the observation that some breeding lines showed longer time to flowering and higher canopy temperature than IR64, suggest that selection for additional physiological traits may result in further improvements of this breeding pool.